Navigating the Privacy Paradox : Balancing AI Advancement and Data Protection in the Digital Age - Venkata Rajesh Krishna Adapa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid advancement of artificial intelligence (AI) technologies has ushered in an era of unprecedented data utilization, raising critical concerns about individual privacy. This article examines the complex interplay between AI development and data protection, exploring the challenges of balancing the need for large-scale data processing with the imperative to safeguard personal information. We analyze current regulatory frameworks, including GDPR and CCPA, and their efficacy in addressing AI-specific privacy issues. The article also evaluates technical measures such as differential privacy, federated learning, privacy-preserving machine learning algorithms, and organizational best practices for responsible data management. By synthesizing computer science, law, and ethics perspectives, we propose a multidisciplinary approach to fostering AI innovation while robustly protecting individual privacy rights. Our findings underscore the need for adaptive regulations, enhanced technical safeguards, and increased collaboration between stakeholders to navigate the evolving landscape of AI and privacy in the digital age.
Keywords: Artificial Intelligence; Data Privacy; Machine Learning Ethics; Privacy-Preserving Algorithms; Data Protection Regulations